Efeito da sobreposição entre ilhas da estratégia tabuleiro de xadrez na porosidade do AISI 316L processado por fusão em leito de pó a laser - Machado, Maicow Roney Fiedler da Costa (2025)
With the increasing adoption of additive manufacturing (AM) due to the simplification of production steps and the possibility of manufacturing complex parts, there is growing attention to the mechanical properties of processed materials. This focus is essential for AM to effectively compete with materials obtained through conventional processes. Laser powder bed fusion (L-PBF) is one of the main AM technologies for processing AISI 316L powder, a widely used material and of interest in this research. In this process, it was found that the primary defect influencing the material’s properties is porosity. A common laser scanning strategy in L-PBF is the so-called “chessboard” strategy, in which the area of a layer to be processed is divided into small squares (islands). This technique helps reduce internal stresses by shortening the laser paths on the islands. However, it can exacerbate porosity, especially in the regions where the islands meet. A solution suggested in the literature to mitigate this problem is shifting the chessboard in the X and Y directions. However, the effect of the overlap between islands in the same layer, both with and without layer-to-layer shifting, has been little studied in relation to porosity in this strategy. Therefore, this work aims to evaluate the porosity correlated with the laser scanning overlap parameters between islands in the same layer, as well as to analyze the effect of chessboard shifting between layers. Test specimens were printed with different overlap values, with or without layer shifting, and porosity was analyzed through image micrography. The results showed a clear relationship between island overlap and porosity. It was found that a 135% overlap normalized the porosity in the region between islands compared to other areas, demonstrating that this is an interesting value for this parameter. Additionally, it was observed that chessboard shifting also contributed to reducing porosity, and the combination of these two strategies presented the lowest porosity levels in the chessboard strategy within the L-PBF process.